2017
DOI: 10.1002/ppsc.201700363
|View full text |Cite
|
Sign up to set email alerts
|

Shape‐ and Trap‐Controlled Nanocrystals for Giant‐Performance Improvement of All‐Inorganic Perovskite Photodetectors

Abstract: In the last few years, all‐inorganic perovskite CsPbBr3 nanocrystals (NCs) have attracted tremendous attention for its high carrier mobility, long carrier diffusion length, excellent visible light absorption, and more importantly superior air stability. In fact, photodetectors (PDs) are designed and fabricated using the CsPbBr3 NCs with very high performance. Herein, by optimizing the NC shape, size, and surface passivation, the CsPbBr3 PDs are developed with an even higher performance. It is found that the PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Moreover, there are also reports suggesting that the A site does not confer any fundamental advantage to the charge carrier mobilities . Hence, it is desirable to replace the fragile organic group with more robust inorganic Cs cations to form more stable CsPb X 3 perovskite material . In fact, there have been studies of CsPb X 3 in terms of its compositional and structural phase stability .…”
Section: Parameters Of the Pscs Based On Different Cspbi2br Films Extmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there are also reports suggesting that the A site does not confer any fundamental advantage to the charge carrier mobilities . Hence, it is desirable to replace the fragile organic group with more robust inorganic Cs cations to form more stable CsPb X 3 perovskite material . In fact, there have been studies of CsPb X 3 in terms of its compositional and structural phase stability .…”
Section: Parameters Of the Pscs Based On Different Cspbi2br Films Extmentioning
confidence: 99%
“…[22][23][24][25] Hence, it is desirable to replace the fragile organic group with more robust inorganic Cs cations to form more stable CsPbX 3 perovskite material. [26][27][28][29][30][31] In fact, there have been studies of CsPbX 3 in terms of its compositional and structural phase stability. [32][33][34] Unfortunately, this Cs replacement brings about a different problem: The desired black CsPbI 3 cubic phase (with narrow bandgap of 1.7 eV) is not the most thermodynamically stable phase at normal operational temperatures, and it may turn into the nonperovskite yellow phase quickly, even in an inert atmosphere.…”
mentioning
confidence: 99%
“…But along with their advantages, the deficiencies were quickly exposed: even though CsPbBr 3 shows good thermal stability, its band gap is as large as 2.3 eV, too large to absorb visible light beyond 540 nm. [17][18][19] Although CsPbI 3 has a more suitable band gap (1.73 eV), it suffers from notorious phase instability. [20][21][22] Later, the dual halide CsPbI 2 Br was developed, and it has great advantages in terms of ambient phase stability and a more suitable band gap (1.91 eV).…”
mentioning
confidence: 99%
“…The optimized device presented R of 10.85 A W −1 , D* of 3.06 × 10 13 Jones, rise/decay times of 44/390 µs, and LDR of 73 dB. Meanwhile, Pang et al synthesized CsPbBr 3 nanocrystals with different shapes, and introduced PCBM to fabricate PDs (see Figure c,d) . They found that the device based on nanoribbons showed better performance compared with those based on QDs and nanocubes, and this could be attributed to the higher mobility and fewer defects.…”
Section: Performance Improvement Strategiesmentioning
confidence: 99%
“…Copyright 2017, The Royal Society of Chemistry. c,d) Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Performance Improvement Strategiesmentioning
confidence: 99%